Effect of geometrical features on the contra-rotating propeller hydrodynamic performances (Journal of Naval Architecture and Marine Engineering, 2020)
New contra-rotating four-bladed DTMB propeller configurations operating in open water are numerically studied to determine their hydrodynamic performances. The unsteady turbulent flow around propellers is modelled by RANS equations with Kω SST model then solved by a CFD code. The computational domain is divided in two blocks linked with a rotating interface. The obtained results show that thrust and efficiency of the contra-rotating (CRP) increase compared to the single propeller, leading to a significant reduction of the propeller diameter. The variation in axial spacing and angular displacement seems to have little effect on the CRP efficiency. The results also show that the thrust can be further improved by adopting a moderate negative twist angle of the rear propeller.Keywords: CRP contra-rotating propeller, axial spacing, angular spacing, twist angle, CFD.